2019
DOI: 10.1115/1.4044897
|View full text |Cite
|
Sign up to set email alerts
|

The Stiffness-Threshold Conflict in Polymer Networks and a Resolution

Abstract: Stiffness and fatigue threshold are important material parameters in load-carrying applications. However, it is impossible to achieve both high stiffness and high threshold for single-network elastomers and single-network hydrogels. As the polymer chain length increases, the stiffness reduces, but the threshold increases. Here, we show that this stiffness-threshold conflict is resolved in double-network hydrogels, where the stiffness depends on the short-chain network, but the threshold depends on the long-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…The G 0 for these three samples is almost the same (∼68 J/m 2 ). This is consistent with the reports by Suo and coworkers showing that the threshold G 0 is determined by the chemically cross-linked polymer network structure (9,13,15), which is the same for the three samples. Furthermore, G 0 has the same order of magnitude as the energy required to rupture the polymer strands across the fracture plane, Γ 0 , predicted by the Lake-Thomas model (32).…”
Section: Respectively With the Global Elongation Ratio λsupporting
confidence: 93%
See 1 more Smart Citation
“…The G 0 for these three samples is almost the same (∼68 J/m 2 ). This is consistent with the reports by Suo and coworkers showing that the threshold G 0 is determined by the chemically cross-linked polymer network structure (9,13,15), which is the same for the three samples. Furthermore, G 0 has the same order of magnitude as the energy required to rupture the polymer strands across the fracture plane, Γ 0 , predicted by the Lake-Thomas model (32).…”
Section: Respectively With the Global Elongation Ratio λsupporting
confidence: 93%
“…Above a threshold of energy release rate G 0 , the crack grows rapidly with the fatigue cycle. It has been revealed that the threshold G 0 is only determined by the primary network structure of the materials, which depends on chemical cross-linking density (13)(14)(15)(16). The antifatigue properties of soft materials are found to be effectively improved by introducing additional structures to the primary network structure, such as crystals (17)(18)(19), composites (20)(21)(22), ordered folded units (23,24), and so on.…”
mentioning
confidence: 99%
“…70,490 Similarly, the long polymer chains can give a relatively high intrinsic fracture energy of the hydrogel. 540 The mechanical properties of the nano-/microfibrous polymer networks are determined by their fibers, interactions of the fibers (e.g., cross-links between fibers), and topologies of the fibrous polymer networks. Therefore, the stretch limit, shear modulus, and intrinsic fracture energy of nano-/microfibrous hydrogels do not follow the coupling relations for the conventional polymer networks (eqs 13 and 14), and therefore they can be independently designed.…”
Section: Unconventional Polymer Network Architecturesmentioning
confidence: 99%
“…A high density of the short polymer chains can give a high initial shear modulus of the hydrogel. While these short chains will be fractured when the hydrogel is highly stretched, the long polymer chains can still maintain the integrity and high stretch limit of the hydrogel. , Similarly, the long polymer chains can give a relatively high intrinsic fracture energy of the hydrogel …”
Section: Unconventional Polymer Networkmentioning
confidence: 99%
“…The low toughness of the pure PAA hydrogel can be well predicted by the classical Lake–Thomas model [ 67 , 68 ]. Due to lacking effective energy dissipation mechanisms around the crack tip, the crack can readily propagate by scissoring polymer chains laying across the crack plane.…”
Section: Results and Discussionmentioning
confidence: 99%